Buddhist approaches to human rights: dissonances and resonances - Meinert, Carmen; Zöllner, Hans-Bernd (Der Mensch im Netz der Kulturen, 2010)
The demonstrations of monks in Tibet and Myanmar (Burma) in recent times as well as the age-old conflict between a predominantly Buddhist population and a Hindu minority in Sri Lanka raise the question of how the issues of human rights and Buddhism are related. The question applies both to the violation of basic rights in Buddhist countries and to the defence of those rights which are well-grounded in Buddhist teachings. The volume provides academic essays that reflect this up to now rather neglected issue from the point of view of the three main Buddhist traditions, Theravada, Mahayana and Vajrayana. It provides multi-faceted and surprising insights into a rather unlikely relationship.